Representações sociais acerca do trabalhador do setor de logístico com mais de 45 anos - Vido, Keli Cristiane (2018)
This study aimed at identifying the social representations that São Paulo workers in the logistics sector who are 45 or older have built about themselves. In order to do this, the Theory of Social Representations, an structural approach proposed by Jean Claude Abric, was used as theoretical support. Data were obtained from a questionnaire applied to 203 workers performing operational, administrative and managerial positions in the logistics sector of companies such as Transnova Transports, Dhl, Veloz and Trucks. These study participants occupied operational, administrative and managerial positions. The metrological path was comprised of three stages: the first one built on two reviews of the literature on academic publications concerning older workers and social representations followed by a qualitative research with the managers of the researched companies aiming to understand this work context and finally a research on the social representations these professionals have built of themselves. This reseach toolabout social representations was based on the use of the Free-word Association Technique (represented by the acronym TALP, in Portuguese) which used inductive warming terms and the inductive term worker who is 45 or older, the central aspect of this study. The analysis of the data collected with TALP makes treaties by means of synonym and are analyzed with the help of the following softwares: Open Evoc and Iramuteq. As this is a research of qualitative nature, one has used synonymy in a structural approach of the words in order to analyze the collected material. The use of prototypical and similarity analyses has allowed the refinement of the constituent terms of the social representation of the researched group, rendering a more accurate understanding of its nucleus. The evidenced results demonstrated and presented by the Verges Framework allowed to identify and analyze the constituent elements of the social representations, that is to say, central nucleus periphary and of contrast. These results were contrasted with the Prototypic Analysis, which allowed us to refine these results. With the similitude analysis, one could understand the co-occurrences established among the constituent elements of social representations. The results indicated elements of the social representations about the logistics sector worker who is 45 or older based on dichotomous and contradictory aspects such as experience and devaluation, dedication and retirement, divided by a set of skills and stereotypes which are both positive and negative. These constituent terms of social representations also show that the workers which were part of the research, although they are able to relate their work context to the conceptual elements of this reality, have a stereotyped understanding of themselves. The set of information obtained allows us to suppose that such social representations are systematically fed by the professionals themselves, who promote the continuity of organizational practices unable of retaining human capital in seniority, since they advocate biological aging linked to the inexorable decline of labor capacities labor and professional disengagement. The study as a contribution has made it possible not only to identify and analyze the constituent elements of these social representations delineated by the worker himself, but also to contribute with these results a reflection on the need to transform organizational policies and practices and create new public policies in Brazil which will be able to ensure the active permanence of the worker from the moment he is 45 years old in the labor market. However, one must highlight that this study has a limitation which refers to the need to expand this kind of research to other Brazilian states and several different sectors, since the social representations investigated here are related to São Paulo workers who are ih the logistics sector, are 45 or older and refers to the representations they have built about themselves. The worker with or over 45 years of the São Paulo logistics sector, built of themselves. In short, identifying, investigating and analyzing the social representations of the older worker in the São Paulo logistics sector allowed us to delineate the response of the social expectation that, in the face of longevity, still reinforces policies and practices which promote the disengagement of these professionals and are incapable of generating the real autonomy of these workers facing their aging process.